A Rare Case of Pure Primary Large Cell Neuroendocrine Carcinoma of the Gallbladder - Rodney E. Shackelford; Ekin Ozluk; Jehan Abdulsattar; Terry C. Lairmore; Quyen Chu; Eric X. Wei (Case Reports in Oncological Medicine)
Primary large cell neuroendocrine carcinoma (LCNEC) of the gallbladder is a rare malignancy which is often associated with non-LCNEC histologic components. Histologically “pure” LCNECs of the gallbladder are exceedingly rare with only 15 cases reported in the medical literature. Clinically, LCNECs present with abdominal pain and jaundice and follow an aggressive course with patients surviving a median of 15 months following initial diagnosis. To our knowledge, we present the 16th case of a histologically pure LCNEC in a 62-year-old African American male who was successfully treated surgically. After discharge, he was subsequently lost to follow-up. Due to the extreme rarity of such disease entity, accurate diagnosis and proper management are essential for the best clinical outcome.